2016
DOI: 10.1111/infa.12166
|View full text |Cite
|
Sign up to set email alerts
|

Infant Neurodevelopment is Affected by Prenatal Maternal Stress: The QF2011 Queensland Flood Study

Abstract: Research shows that prenatal maternal stress (PNMS) negatively affects a range of infant outcomes; yet no single study has explored the effects of stress in pregnancy from a natural disaster on multiple aspects of infant neurodevelopment. This study examined the effects of flood‐related stress in pregnancy on 6‐month‐olds' neurodevelopment and examined the moderating effects of timing of the stressor in gestation and infant sex on these outcomes. Women exposed to the 2011 Queensland (Australia) floods in pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 80 publications
2
25
0
Order By: Relevance
“…As its effect reduced further after controlling for maternal depressive symptoms in the adjusted model, this may indicate a specific association of flood‐related PNMS with this outcome, beyond the influence of nonflood stressful life events during pregnancy. Although association of stress during pregnancy with aspects of child social functioning conflicts with some existing studies (Karam et al., ; Kvalevaag et al., ), the current results are consistent with delayed acquisition of social competencies in infants of mothers higher in prenatal trait anxiety (Koutra, ) and maternal subjective distress in the QF2011 cohort (Simcock, Kildea, et al., ; Simcock, Laplante, et al., ). Together, these findings lend support to an enduring effect of PNMS on offspring social–emotional development from early infancy to toddlerhood.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As its effect reduced further after controlling for maternal depressive symptoms in the adjusted model, this may indicate a specific association of flood‐related PNMS with this outcome, beyond the influence of nonflood stressful life events during pregnancy. Although association of stress during pregnancy with aspects of child social functioning conflicts with some existing studies (Karam et al., ; Kvalevaag et al., ), the current results are consistent with delayed acquisition of social competencies in infants of mothers higher in prenatal trait anxiety (Koutra, ) and maternal subjective distress in the QF2011 cohort (Simcock, Kildea, et al., ; Simcock, Laplante, et al., ). Together, these findings lend support to an enduring effect of PNMS on offspring social–emotional development from early infancy to toddlerhood.…”
Section: Discussionsupporting
confidence: 84%
“…Results to date suggest that children exposed to the Queensland floods prenatally demonstrate alterations in development across a range of domains (Austin et al., ; Moss et al., ; Simcock, Laplante, et al., ). Regarding behavioral development, mothers reporting greater flood‐related objective hardship (e.g., extent of property damage), and subjective stress (peritraumatic, posttraumatic, and cognitive reactions) were more likely to describe their 6‐month‐old infants as exhibiting more difficult aspects of temperament, with the specific impacts dependent on infant sex and timing of exposure (Simcock, Elgbeili, et al., ).…”
Section: Natural Disasters As “Natural Experiments”mentioning
confidence: 99%
See 1 more Smart Citation
“…Three papers reported data from the Queensland Flood Study. Simcock et al ( N  = 115) found a sex interaction in the association between disaster-related PNMS and child problem solving at age 6 months, with girls having poorer problem solving than boys at high levels of prenatal stress [48]. In contrast, Moss et al ( N  = 145) found no evidence of sex dependence in the association between PNMS and adolescent cognitive development [66].…”
Section: Resultsmentioning
confidence: 99%
“…37 Even within the QF2011 cohort, we have found that higher subjective stress has predicted better fine motor development at 2 months of age 20 and improved problem solving among boys at 6 months of age. 38…”
Section: Main Effectsmentioning
confidence: 99%